Young Children Have Difficulty Predicting Future Preferences in the Presence of a Conflicting Physiological State. Issue 4 (15th August 2015) - Mahy, Caitlin E. V.
Abstract : This study examined children's predictions about their future preferences when they were in two different physiological states (thirsty and not thirsty). Ninety 3‐ to 7‐year‐olds were asked to predict what they would prefer tomorrow: pretzels to eat or water to drink after having consumed pretzels, and again after having had the opportunity to quench their thirst with water. Results showed that although children initially preferred pretzels to water at baseline, they more often indicated that they would prefer water the next day after they had consumed pretzels. After consuming water, however, the same children indicated they would prefer pretzels the next day. Children's verbal justifications for their choices rarely made reference to their current or future states, but rather justifications were more likely to make reference to their general preferences when they were no longer thirsty compared to when they were thirsty. Results suggest that current physiological states have a powerful influence on future preferences. The findings are discussed in the context of the development of episodic foresight, the Bischof‐Kohler hypothesis, and the important and often overlooked role that children's current states play in future decision making. Copyright © 2015 John Wiley & Sons, Ltd.